Isotopic signatures of biotic and abiotic N 2 O production and consumption in the water column of meromictic, ferruginous Lake La Cruz (Spain) - Jana Tischer; Jakob Zopfi; Claudia Frey; Paul M. Magyar; Andreas Brand; Kirsten Oswald; Corinne Jegge; Caitlin H. Frame; María R. Miracle; Xavier Sòria‐Perpinyà; Eduardo Vicente; Moritz F. Lehmann (Limnology and Oceanography, 2022)
Lakes can be important sources of the potent greenhouse gas nitrous oxide (N 2 O) to the atmosphere, but to what extent abiotic processes may contribute to lacustrine N 2 O production remains uncertain. We assessed pathways of N 2 O production and reduction in the water column of meromictic and iron‐rich Lake La Cruz, Spain, including chemodenitrification‐induced N 2 O formation via the reaction of reactive nitrogen (N) (e.g., ) with ferrous iron (Fe[II]). In the oxic waters (~8–10 m), N 2 O concentrations above atmospheric equilibrium were associated with comparatively low δ 15 N‐N 2 O, high , and high N 2 O 15 N‐site‐preference (SP) values (up to ~29‰), suggesting N 2 O production by nitrification. N 2 O concentrations were highest (23–33 nM) near the depth of oxygen depletion (~11–14.5 m), likely due to production by nitrifier denitrification and/or denitrification, as indicated by decreasing SP values (as low as 12‰). Further below (~14.5–17 m), N 2 O consumption was indicated by increasing SP values and a δ 18 O‐vs.‐δ 15 N relationship (1.8–2.9) typical for stand‐alone N 2 O reduction. The coupled N‐vs.‐O isotope signatures thus highlight the spatial, redox‐dependent separation of incomplete and complete denitrification. In incubations with sterile‐filtered lake water and 15 N‐labeled or unlabeled substrate, was reduced by Fe 2+ to N 2 O, even at low nitrite concentrations (5 μ M ). In the water column, the spatial separation of and Fe(II) during our samplings appears to preclude elevated rates of chemodenitrification, but during periods of overlapping and Fe(II) in Lake La Cruz, and potentially in other lakes, its distinct N 2 O δ 18 O‐vs.‐δ 15 N relationship of ~1 : 1, as experimentally determined, could help to detect it.

Nitrogen and oxygen isotopomeric constraints on the sources of nitrous oxide and the role of submarine groundwater discharge in a temperate eutrophic salt‐wedge estuary - Wei Wen Wong; Moritz F. Lehmann; Thomas Kuhn; Caitlin Frame; Seng Chee Poh; Ian Cartwright; Perran L.M. Cook (Limnology and Oceanography, 2021)
Estuaries have been identified as sources of nitrous oxide (N 2 O) emissions to the atmosphere but questions remain as to which production pathway(s) govern the oversaturation of N 2 O observed in most estuaries worldwide. Here, we use a suite of nitrate and N 2 O isotopes, as well as the 15 N site preference signatures of N 2 O to assess (1) the relative importance of different N 2 O production pathways in a eutrophic groundwater‐impacted salt‐wedge estuary and the aquifers underlying the estuary and (2) the influence of groundwater input on the overall N 2 O saturation in the estuary. This is one of the few studies to examine the effect of groundwater–surface water interaction on N 2 O cycling using N 2 O isotopes. The site preference values of N 2 O in the deep aquifer below the estuary were distinctive (83‰ ± 25‰) and were much higher than in either surface water (21‰ ± 6‰) or shallow groundwater (44‰ ± 8‰), suggesting the influence of multiple biotic and/or abiotic processes which proceed through multiple cycles, and/or the occurrence of a yet unidentified N 2 O production pathway. Isotope endmember considerations revealed that nitrifier‐denitrification was the major N 2 O production pathway within the shallow aquifer whereas within the estuarine water column, N 2 O saturation was governed by chemodenitrification and discharge of N 2 O‐laden submarine groundwater. Our study not only emphasizes the substantial, yet often underappreciated role of submarine groundwater discharge in estuarine N 2 O budgets, but also highlights the need to reevaluate the importance of the noncanonical denitrification pathways (i.e., chemodenitrification and nitrifier‐denitrification) in controlling the overall N 2 O production from estuarine and groundwater environments.

Basin‐scale inputs of cobalt, iron, and manganese from the Benguela‐Angola front to the South Atlantic Ocean - Abigail E. Noble; Carl H. Lamborg; Dan C. Ohnemus; Phoebe J. Lam; Tyler J. Goepfert; Chris I. Measures; Caitlin H. Frame; Karen L. Casciotti; Giacomo R. DiTullio; Joe Jennings; Mak A. Saito (Limnology and Oceanography, 2012)
We present full‐depth zonal sections of total dissolved cobalt, iron, manganese, and labile cobalt from the South Atlantic Ocean. A basin‐scale plume from the African coast appeared to be a major source of dissolved metals to this region, with high cobalt concentrations in the oxygen minimum zone of the Angola Dome and extending 2500 km into the subtropical gyre. Metal concentrations were elevated along the coastal shelf, likely due to reductive dissolution and resuspension of particulate matter. Linear relationships between cobalt, N 2 O, and O 2 , as well as low surface aluminum supported a coastal rather than atmospheric cobalt source. Lateral advection coupled with upwelling, biological uptake, and remineralization delivered these metals to the basin, as evident in two zonal transects with distinct physical processes that exhibited different metal distributions. Scavenging rates within the coastal plume differed for the three metals; iron was removed fastest, manganese removal was 2.5 times slower, and cobalt scavenging could not be discerned from water mass mixing. Because scavenging, biological utilization, and export constantly deplete the oceanic inventories of these three hybrid‐type metals, point sources of the scale observed here likely serve as vital drivers of their oceanic cycles. Manganese concentrations were elevated in surface waters across the basin, likely due to coupled redox processes acting to concentrate the dissolved species there. These observations of basin‐scale hybrid metal plumes combined with the recent projections of expanding oxygen minimum zones suggest a potential mechanism for effects on ocean primary production and nitrogen fixation via increases in trace metal source inputs.